Evaluasi Biaya Dan Kebutuhan Alat Angkut Dan Alat Muat Pengupasan Lapisan Tanah Penutup (Overburden) Pit B PT. Bina Bara Sejahtera Kecamatan Ulok Kupai, Kabupaten Bengkulu Utara, Provinsi Bengkulu - Fachrur Isgianda; Sumarya Sumarya; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2018)
PT. Bina Bara Sejahtera targets overburden demolition of 175.000 bcm/month, but all that has not been achieved. Efforts to achieve the production target of overburden from the work of mechanical devices is to calculate the actual work efficiency and increase the efficiency of mechanical work. Actual work efficiency Komatsu PC300 Excavators that work on fleet 1 53,91%, fleet 2 52,22%, fleet 3 50,53% and fleet 4 51,47%, Volvo BMA35C ADT on fleet 1 55,15%, fleet 2 50,81%, fleet 3 50,36% and fleet 4 is 52,08%. Work efficiency after increasing efficiency Komatsu PC300 Excavators that work on fleet 1 67,97%, fleet 2 67,22, fleet 3 64,47% and fleet 4 66,47%. Volvo BMA35C ADT on fleet 1 74,91%, fleet 2 67,22%, fleet 3 64,47% and fleet 4 66,47%. Actual production on the dismantling of fleet 1 overburden 28.944.24 bcm/month, fleet 2 28.449.67 bcm/month, fleet 3 22.955.50 bcm/month and fleet 4 36.844.61 bcm/month, after increasing work efficiency dismantling fleet overburden 1 53.402 bcm/month, fleet 2 52.168.92 bcm/month, fleet 3 40.365,49 bcm/month and fleet 4 60.548.61 bcm/month. Operating cost of disassembling operations for Volvo BMA35C Komatsu PC300 and ADT Excavator overburden Rp.2.317.249.728. Operating cost after increasing work efficiency Rp.3.019.797.720. The actual overburden per Bcm fee is Rp.19.772/bcm after evaluation Rp. 16.125/bcmKeywords: Cycle Time,Stripping Overburden, Cost of overburden, work efficiency